Anti-Inflammatory Application of Farnesol: a mapping based on scientific articles and patents - Silva, Regina Célia da (2024)
Farnesol is a natural organic compound present in essential oils from various plants. This study aimed at a comprehensive analysis of patent documents and scientific articles related to the anti-inflammatory potential of farnesol. The research adopted a descriptive and prospective approach encompassing the search for scientific articles in databases such as Pubmed, Virtual Health Library (VHL), Science Direct and Web of Science. Patent applications were investigated on the bases of the National Institute of Industrial Property (INPI) and the World Intellectual Property Organization (WIPO). The results pointed to a growing interest in the use of farnesol as an anti-inflammatory agent. All studies analyzed incorporated Biotechnology to improve the efficacy and delivery of farnesol, highlighting the relevance of Nanotechnology in this context. Therefore, farnesol has a notable anti- inflammatory potential and can be explored in the development of medicines for inflammatory diseases and represents an innovative alternative in the treatment of inflammatory diseases.